2022
DOI: 10.3390/children9030426
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Predictors and Outcomes of Noninvasive Ventilation Failure in Very Preterm Infants

Abstract: Non-invasive ventilation (NIV) is now considered the first-line treatment for respiratory distress syndrome in preterm infants. We aimed to evaluate the rates of non-invasive ventilation failure rate in very preterm infants, as well as to identify its predictors and associated outcomes. We designed a single-center retrospective cohort study including infants ≤32 weeks gestational age and ≤1500 g. The NIV failure was defined as the need for intubation at <72 h of life. After applying inclusion and exclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Also, other studies by Rocha et al, [14] and De Jaegere et al, [15] showed failure rates of 20.6% -34% in neonates with gestational age less than 36 weeks. Fernandez-Gonzalez SM et al, [16] reported in their study a CPAP failure rate of 64% in preterm neonates of gestational age less than 28 weeks compared to a rate of 8.5% in neonates with gestational age above 28 weeks. In accordance, low gestational age seems to be the most critical risk factor of CPAP failure [17,18] .…”
Section: Discussionmentioning
confidence: 90%
“…Also, other studies by Rocha et al, [14] and De Jaegere et al, [15] showed failure rates of 20.6% -34% in neonates with gestational age less than 36 weeks. Fernandez-Gonzalez SM et al, [16] reported in their study a CPAP failure rate of 64% in preterm neonates of gestational age less than 28 weeks compared to a rate of 8.5% in neonates with gestational age above 28 weeks. In accordance, low gestational age seems to be the most critical risk factor of CPAP failure [17,18] .…”
Section: Discussionmentioning
confidence: 90%
“…Recent non-invasive ventilator (NIV) strategies have reduced the incidence of endotracheal intubation and duration of mechanical ventilator support in NICU management 3,4 . While the increasing use of NIV includes high-flow nasal cannula (HFNC), nasal continuous positive airway pressure (NCPAP), bilevel positive airway pressure (BIPAP), and non-invasive positive pressure ventilation (NIPPV) in neonates with respiratory difficulties, a significant proportion fail on NIV support and require intubation within the first few days of birth, especially in preterm infants [5][6][7] .Neonatal respiratory distress syndrome (RDS) is a major source of morbidity in NICU. Ordinary treatments include mechanical ventilation and surfactant replacement therapy 8,9 .…”
mentioning
confidence: 99%